Comparative analysis of neutralization assays performed using live SARS-CoV-2 virus and pseudovirus to assess immunogenicity of a bivalent SARS-CoV-2 protein vaccine in humans - Gao, Cuige; Yi, Jiang; Baidoo, Adam; Liu, Dongfang; Li, Jing; Li, Dongyang; Li, Jian; Zhou, Qiang; Xie, Liangzhi (Frontiers in Immunology, 2025)
ObjectivesThe rapid emergence of SARS-CoV-2 prompted accelerated vaccine development, with neutralization assays serving as essential tools to evaluate vaccine-induced immune responses.MethodsA post-hoc analysis of a Phase I/II trial evaluated the immunogenicity of a bivalent SARS-CoV-2 protein vaccine. We assessed vaccine immunogenicity using live virus neutralization assays (LVNA) and pseudotyped virus neutralization assays (PVNA) to measure antibody responses against different variants, including Alpha B.1.1.7, Beta B.1.351, and Delta B.1.617.2. Various statistical techniques, including correlation coefficients, regression models, and Bland–Altman plots, were employed to assess the relationship between antibody titers from the two assays.ResultsWe analyzed 324 samples for Alpha and Beta variants and 505 for Delta. Compared with LVNA, the sensitivity and specificity of PVNA were over 90% across all variants, with accuracy rates of 98.8% for Alpha, 99.1% for Beta, and 94.3% for Delta. The Pearson correlation between PVNA and LVNA was strong for Alpha (CORR = 0.9614), Beta (CORR = 0.9517), and Delta (CORR = 0.9072). Bland-Altman plots and Kernel density plots indicated good agreement between PVNA and LVNA.ConclusionsOur findings demonstrate a strong correlation between PVNA and LVNA results, supporting PVNA as a safe, scalable, and reliable surrogate for LVNA in evaluating vaccine immunogenicity.